177 dB Linear Dynamic Range Pixels of Interest DSLR CAOS Camera - Nabeel A. Riza; Mohsin A. Mazhar (IEEE Photonics Journal, 2019)
For the first time, demonstrated is an extreme linear Dynamic Range (DR) Pixels of Interest (POI) [i.e., Coded Access Optical Sensor (CAOS)] Digital Single Lens Reflex (DSLR) camera design that engages three different types of photosensors within one optomechanical assembly to smartly identify POI across a one billion to one light irradiance range. A pixelated CMOS sensor provides a limited DR and linearity image by engaging a moveable mirror placed between the Digital Micromirror Device (DMD) and the frontend imaging lens. Next using DMD control, non-POI light is directed away from the chosen point photodetector (PD) engaged for high DR POI image recovery, giving the PD an improved use of quantum well capacity. For brighter POI, a solid state photodiode point PD with an electronic gain controlled amplifier is engaged while for weaker light POI, a photomultiplier tube (PMT) with variable optical gain is deployed. POI imaging is achieved using time-frequency CAOS modes via DMD control and time-frequency correlation and spectral digital signal processing. A 123.4 dB linear DR POI recovery is achieved for a custom incoherent white light 36-patch target while a record 177 dB linear DR recovery is demonstrated for a single patch 633 nm laser target. For the first time, a 1023 POI frame, real-time 48 frames/s update rate CAOS imaging is demonstrated for tracking a changing focal spot moving laser target.